Optical identification of single- and few-layer MoS2 sheets - Zhang, Qing (2013)
A simple approach is developed to identify the layer number of 2D MoS2 sheets. By using an optical imaging method combined with image analysis software, a high-contrast image of the MoS2 sheets can be extracted from the red (R) channel of the color optical microscopy image. The value of the intensity difference in the grayscale image of the R channel between MoS2 sheets (1–3 layers) and the SiO2 substrate can be used to identify the layer number of the sheet.